Substrate characteristic bacterial fatty acid production based on amino acid assimilation and transformation in marine surface sediments from the Wadden Sea, Germany - Rebecca F Aepfler; Solveig I Bühring; Marcus Elvert (PANGAEA, 2020)
Polar lipid-derived fatty acids (PLFAs) and their stable carbon isotopes are frequently combined to characterize microbial populations involved in the degradation of organic matter, offering a link to biogeochemical processes and carbon sources used. However, PLFA patterns derive from multiple species and may be influenced by substrate types. Here, we investigated such dependencies by monitoring the transformation of position-specifically 13C-labeled amino acids (AAs) in coastal marine sediments dominated by heterotrophic bacteria. Alanine was assimilated into straight-chain FAs, while valine and leucine incorporation led to the characteristic production of even- and odd-numbered iso-series FAs. This suggests that identical microbial communities adjust lipid biosynthesis according to substrate availability. Transformation into precursor molecules for FA biosynthesis was manifested in increased 13C recoveries of the corresponding volatiles acetate, isobutyrate and isovalerate of up to 39.1%, much higher than for PLFAs (<0.9%). A significant fraction of 13C was found in dissolved inorganic carbon (up to 37.9%), while less was recovered in total organic carbon (up to 17.3%). We observed a clear discrimination against the carboxyl C, whereby C2 and C3 positions were preferentially incorporated into PLFAs. Therefore, position-specific labeling is an appropriate tool for reconstructing the metabolic fate of protein-derived AAs in marine environments.